AUTHORITY OF A NOTARY IN MAKING A DEED CONCERNING THE POSTPONEMENT OF THE DISTRIBUTION OF INHERITANCE TO THE HEIRS - Iin Ervian Indri Sejati; Rahmatul Hidayati; Budi Parnomo (International Journal of Cultural and Social Science, 2026)
This research is motivated by the lack of explicit regulations regarding the authority of notaries in making deeds of postponement of inheritance distribution which has the potential to cause legal uncertainty and disputes. This research aims to analyze the authority of notaries, the reasons for postponement, and legal protection for the parties. The method used is normative legal research with a statutory, conceptual, and case approach through literature study and analysis of court decisions. The results of the research indicate that notaries are authorized to formalize postponement in authentic deeds based on Article 15 of the Notary Law and a binding agreement according to Article 1338 of the Civil Code. The postponement is carried out for legitimate reasons as stated in Article 1066 and Article 1074 of the Civil Code as well as the notary's duty of prudence. This research concludes that postponement is a legitimate preventive mechanism based on Article 833, Article 955, and Article 1865 of the Civil Code as well as Article 16 and Article 65 of the Notary Law to ensure legal certainty and protection.